GENERAL CONSIDERATIONS ON THE IMPACT OF PROPERTY ON THE ECONOMIC AND SOCIAL STATUS OF PEOPLE - DIACONESCU, Amelia Mihaela; BANU, Cristina (Annals of Spiru Haret University. Economic Series, 2018)
Property is indissolubly linked to people's lives, forming part of it, being a permanent problem and occupying a particularly important place in economic, social, political and philosophical science. Through the structure outlined in this short study, we are also trying to analyze the impact of ownership on people's economic and social status, relative to the concept of property and economic freedom. So, the impact of property as a multiple social relationship on the social status of people is relevant, namely the link between property and economic freedom, property and social justice, property and equality/inequality in society.